1996
DOI: 10.1111/j.1525-1594.1996.tb04412.x
|View full text |Cite
|
Sign up to set email alerts
|

Regenerated Cellulose‐Based Hemodialyzers with Immobilized Proteins as Potential Devices for Extracorporeal Immunoadsorption Procedures: An Assessment of Protein Coupling Capacity and In Vitro Dialysis Performances

Abstract: The development of immunoadsorbents usable with whole blood should offer the potential for making significant improvements in extracorporeal immunoadsorption procedures. In contrast to traditional chromatographic media, these hemocompatible matrices could be used without requiring the previous step of the separation of blood cells and plasma. Conventional hemodialyzers seem to be particularly appropriate for such a purpose. This paper describes a feasibility study of the preparation of immunoaffinity supports,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…These values were respectively about 1.43 and 1.17 times of the untreated PAN membrane. In the literature, Laurent et al [2] reported that the Cuprophan hollow fiber coupled with bovine serum albumin (BSA) showed a slight increase in the ultrafiltration coefficient. Fig.…”
Section: Surface Modification Of Pan Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…These values were respectively about 1.43 and 1.17 times of the untreated PAN membrane. In the literature, Laurent et al [2] reported that the Cuprophan hollow fiber coupled with bovine serum albumin (BSA) showed a slight increase in the ultrafiltration coefficient. Fig.…”
Section: Surface Modification Of Pan Membranesmentioning
confidence: 99%
“…Many studies have aimed to improve hemocompatibility of biomaterials by surface modification [1][2][3][4][5][6][7]. The most widely used blood anticoagulant, heparin, can catalytically increase the rate that antithrombin III (ATIII) inhibits thrombin and some other coagulation proteases [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of membrane materials with a greater affinity for adsorption of beta-2-microglobulin could theoretically result in higher removal rates than could be achieved by convection and diffusion alone. As a logical extension, it has been proposed to immobilize proteins on the surface of dialysis membranes to act as immunoadsorptive devices for beta-2-microglobulin removal [12]. In both of these cases, the potential for beta-2-microglobulin removal by adsorption is limited by the surface area available for adsorption.…”
Section: Adsorption As a Mechanism Of Large Solute Removalmentioning
confidence: 99%
“…Also, the application of immunoadsorption principles to the treatment of DRA has attracted many research interests during the past decades, and a variety of techniques and ingenuity have been combined with the inherent unique advantages of immunoadsorption to create useful, promising materials and modalities for the removal of β‐2M. For example, remarkable advances include production of monoclonal antibodies specific to β‐2M (18), regenerated cellulose‐based hemodialyzers with immobilized proteins (19), and an immunoaffinity‐based extracorporeal vortex flow plasmapheretic reactor (20). These achievements suggest the future potentials of reducing abnormally high levels of β‐2M in uremic blood by immunoadsorption.…”
mentioning
confidence: 99%